New Five Year Plan (1978-83) Sector General Education Draft Annual Plan 1978-79. Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
The Andaman and Nicobar Islands occupy a unique position as a far flung territory of our country. It is a group of about 329 islands occupying an area of about 8293 sq kms. The islands are situated at a distance of 1200 kms from Calcutta and Madras. There are 4 sub divisions and 7 Tahsils in these Islands; because only about 55 islands are inhabited and it is in the villages of these scattered islands. That we are required to provide education facilities.
Andaman and Nicobar Administration